Closed-loop control of gamma oscillations in the amygdala demonstrates their role in spatial memory consolidation - Vasiliki Kanta (Nature Portfolio, 2019)
Gamma oscillations have been proposed to underlie many cognitive and memory processes, but it has proven difficult to directly test this by manipulating them. Here, in rats, the authors show that manipulation of gamma oscillations in the amygdala affects memory consolidation.